(untitled) (Historia, 2021)
The text published as Mein Freund Maleboch is the section of Berlin missionary Christoph Sonntag’s dairy, which describes the Boer conquest of the Bahananwa of Blauberg during the winter of 1894 in the Northern Province of present-day South Africa. The actual transcription of the diary is preceded by a 21-page introduction, jointly compiled by Van der Heyden and Konrad Sonntag, the son of the missionary. This informative section contextualises the Boer-Bahananwa conflict chronologically and geographically.